Seni Memilih Kata dalam Al-Qur'an: Kajian Tafsir Bayani terhadap Diksi Khauf dan Khasyyah: The Art of Word Choice in the Qur'an: A Bayānī Analysis of the Diction of Khauf and Khasyyah - Qarinah Qarinah; Rosmini Rosmini; Rahmi Damis (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2026)
This study aims to analyze the lexical meanings of the Qur’ānic terms khauf and khasyyah in the Arabic lexicographical tradition, examine their usage in Qur’ānic verses through the perspective of Tafsir Bayānī, and identify their similarities and differences through a comparative semantic analysis. This research employs a library research method using a semantic approach and the perspective of Tafsir Bayānī. The primary data consist of Qur’ānic verses containing the terms khauf and khasyyah, along with their interpretations in selected Qur’ānic commentaries, while the secondary data are drawn from Arabic lexicographical works and relevant scholarly literature. The data were analyzed using a descriptive-comparative method to explore the lexical meanings, contextual meanings, and semantic relationships of the two terms. The findings indicate that khauf refers to fear arising as a response to threats, punishment, or undesirable consequences, whereas khasyyah denotes fear rooted in knowledge, reverence, and awareness of Allah's greatness. The Tafsir Bayānī analysis demonstrates that the Qur’ān employs these two terms deliberately in accordance with their respective semantic contexts. Although both are commonly translated as "fear," khauf and khasyyah are not absolute synonyms and therefore cannot be used interchangeably in every Qur’ānic context. These findings highlight the precision of the Qur’ān's lexical choices as one of the manifestations of its linguistic inimitability.